زمرة البيان التام الموجه الدوري من المرتبة pn حيث p أولى و n صحيح موجب (Latakia University Journal -Basic Sciences Series, 2018)
سنجد في هذا البحث أن زمرة الأوتومورفيزم للبيان التام الموجه الدوري ألتربيعي تساوي الزمرة نصف الخطيةL (n , p) الجزئية في الزمرة الخطية العامة GL(n , p) وذلك بالاعتماد على نظرية الزمر البدائية القابلة للحل في زمرة التباديل وعلى الزمر الجزئية البدائية القابلة للحل العظمى في الزمرة الخطية العامة  .GL(n ,p) In this paper, we will prove that the group of cyclotomic tournament is equal to semilinear subgroup of general linear group GL(n, p). However, we have used the theory of permutation groups and maximal solvable irreducible  subgroup of general linear group GL(n, p).